Atom transfer radical polymerization by solvent-stabilized (Me3TACN)FeX2: a practical access to reusable iron(ii) catalysts. Issue 5 (15th December 2015) - Nakanishi, So-ichiro; Kawamura, Mitsunobu; Sunada, Yusuke; Nagashima, Hideo
Abstract : A new Fe(ii ) complex, (Me3 TACN)FeBr2 (κ-NCMe), was prepared as an efficient and reusable catalyst for atom transfer radical polymerization. Abstract : A new Fe(ii ) complex (Me3 TACN)FeBr2 (κ-NCMe), which is stabilized by a weakly coordinating solvent, was prepared as an efficient and reusable catalyst for atom transfer radical polymerization (ATRP) of styrene, MMA, and BA. The complex was conveniently generated from either [(Me3 TACN)Fe(μ-Br)3 (Me3 TACN)] + [Br] − or a mixture of FeBr2 and Me3 TACN in MeCN.